1998
DOI: 10.1002/elps.1150190416
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial phylogeny based on comparative sequence analysis (review)

Abstract: Comparative sequence analysis of small subunit rRNA is currently one of the most important methods for the elucidation of bacterial phylogeny as well as bacterial identification. Phylogenetic investigations targeting alternative phylogenetic markers such as large subunit rRNA, elongation factors, and ATPases have shown that 16S rRNA-based trees reflect the history of the corresponding organisms globally. However, in comparison with three to four billion years of evolution the phylogenetic information content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
557
2
10

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 719 publications
(579 citation statements)
references
References 25 publications
10
557
2
10
Order By: Relevance
“…Sequences (500-600 bp) of selected clones for 16S rRNA genes, pmoA, mmoX and coxL were obtained using the University of Warwick Central Molecular Biology Services Laboratory. Sequences from the NCBI database that were closely related to clone sequences and excised DGGE sequences in this study were identified by ARB (Ludwig et al, 1998) and Basic Local Alignment Search Tool (Altschul et al, 1990). Partial sequences of 16S rRNA were imported into an ARB database (Ludwig et al, 1998) and pre-aligned against the closest relative and alignments were manually checked for consistency and valid secondary structure.…”
Section: Pcr and Denaturing Gradient Gel Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences (500-600 bp) of selected clones for 16S rRNA genes, pmoA, mmoX and coxL were obtained using the University of Warwick Central Molecular Biology Services Laboratory. Sequences from the NCBI database that were closely related to clone sequences and excised DGGE sequences in this study were identified by ARB (Ludwig et al, 1998) and Basic Local Alignment Search Tool (Altschul et al, 1990). Partial sequences of 16S rRNA were imported into an ARB database (Ludwig et al, 1998) and pre-aligned against the closest relative and alignments were manually checked for consistency and valid secondary structure.…”
Section: Pcr and Denaturing Gradient Gel Electrophoresismentioning
confidence: 99%
“…Sequences from the NCBI database that were closely related to clone sequences and excised DGGE sequences in this study were identified by ARB (Ludwig et al, 1998) and Basic Local Alignment Search Tool (Altschul et al, 1990). Partial sequences of 16S rRNA were imported into an ARB database (Ludwig et al, 1998) and pre-aligned against the closest relative and alignments were manually checked for consistency and valid secondary structure. The dendrogram was derived using maximum likelihood (Axml in ARB) based on alignment columns corresponding to Escherichia coli positions 166-625.…”
Section: Pcr and Denaturing Gradient Gel Electrophoresismentioning
confidence: 99%
“…3), tentatively named 'Solibacter usitatus' (http://jgi.doe.gov), with sequence similarities of only 81.7-82.6 %. Although the phylogenetic definition of a genus has been a matter of debate (Wayne et al, 1987), a value of 95 % 16S rRNA gene sequence similarity has previously been suggested to delineate different prokaryotic genera (Ludwig et al, 1998). Furthermore, bootstrap support for the separate cluster encompassing strains Jbg-1 T and Wbg-1 T and three additional sequences was high ( Fig.…”
mentioning
confidence: 92%
“…Oligonucleotide probes were designed with the ARB software package (Ludwig et al, 1998), and rRNA sequences were obtained in an aligned form from the Ribosomal Database Project (RDP) (Maidak et al, 1997) supplemented with newly deposited rRNA sequences from GenBank. Fluorescein-labelled oligonucleotides against selected specific target sequences of E. faecalis and E. faecium were synthesized commercially (Eurogentec) and tested for specificity against the set of reference organisms listed in Table 1. All strains were cultured in the appropriate fluid medium until exponential phase; this medium was diluted 1 : 50 in PBS (8 g NaCl l À1 , 0 .…”
Section: Methodsmentioning
confidence: 99%